Prevention of Underage Marriage with the Purpose of Creating Household Peace Based on a Review of FIQH Law and Civil Law - Lilis Handayani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to describe the prevention of underage marriages with the aim of creating domestic peace based on a review of fiqh law and civil law. The purpose of this research is to educate readers to carry out marriages at the age set by the government, this type of research is qualitative which seeks to reveal phenomena phenomena that are currently developing in the masses, data collection techniques include observation, unstructured interviews, after the data is obtained, an in-depth analysis is carried out. Based on the results of the research, it has been found that the following are civil law instruments regulated by regulations and legal mechanisms set by the government, while fiqh law must fulfill the pillars of marriage, the age of marriage must follow the provisions set by the government, the trigger for early marriage is the family factor digital technology factors, promiscuity factors and cultural factors